Deconstruction of Children's Education in the Digital Era in the Perspective of the Qur'an (Surat An-Nisa Verse 9) and Hadith - Saripudin; Tulus Musthofa; Nur Saidah (Al-Fadlan: Journal of Islamic Education and Teaching, 2024)
Education is a key factor in human life; quality education can improve the standard of living both spiritually and materially. Without education, humans will only be like animals. In this modern era or globalization, many criminal incidents involve children. Elementary school children often bully their younger siblings, while in junior high school, they can fight their parents and do things like stealing their friends' belongings. In high school, sometimes they are together with the opposite sex who are not mahram without shame, involved in brawls between students, illegal racing, motorcycle gangs, free association, drugs, and other disturbing behaviors. Therefore, this study offers a solution to these problems. The Qur'an, Surah An-Nisa Verse 9 related to education aims to build a better generation. The purpose of this research is to: 1) Find out the meaning of the Qur'an, Surah An-Nisa verse 9, and 2) Understand the meaning of the words Dzurriyatan Dhiafan and Qoulan Sadiidan. This study uses a library study method. The explanation in this scientific paper uses a Content Analysis approach, namely an in-depth study of written content contained in print media. Information is obtained from various library sources, including books, interpretations, and scientific works that discuss the letter An-Nisa verse 9. The data sources used are secondary data obtained from libraries, journals, and other sources of information. The steps for collecting information are documentation, as well as the reading process, also analyzing various interpretations, books, journals, and other related information. The results of the research show that the Qur'an, Letter An-Nisa verse 9 emphasizes the responsibility of parents for the future generation related to material aspects. However, verse 9 also emphasizes that obligations towards offspring are not only limited to material things, but also include non-material things such as education and spiritual development. In addition, the concept of education contained in the letter An-Nisa verse 9 indicates that parents are responsible for educating their children to have better attitudes, behaviors, and characters in the future. This shows the importance of parental piety in children's education, as well as the teaching steps that must be implemented.